A two-metal ion mechanism operates in the hammerhead ribozyme-mediated cleavage of an RNA substrate - Lott, William B. (The National Academy of Sciences, 1998)
Evidence for a two-metal ion mechanism for cleavage of the HH16 hammerhead ribozyme is provided by monitoring the rate of cleavage of the RNA substrate as a function of La(3+) concentration in the presence of a constant concentration of Mg(2+). We show that a bell-shaped curve of cleavage activation is obtained as La(3+) is added in micromolar concentrations in the presence of 8 mM Mg(2+), with a maximal rate of cleavage being attained in the presence of 3 μM La(3+). These results show that two-metal ion binding sites on the ribozyme regulate the rate of the cleavage reaction and, on the basis of earlier estimates of the K(d) values for Mg(2+) of 3.5 mM and >50 mM, that these sites bind La(3+) with estimated K(d) values of 0.9 and >37.5 μM, respectively. Furthermore, given the very different effects of these metal ions at the two binding sites, with displacement of Mg(2+) by La(3+) at the stronger (relative to Mg(2+)) binding site activating catalysis and displacement of Mg(2+) by La(3+) at the weaker (relative to Mg(2+)) (relative to Mg(2+)) binding site inhibiting catalysis, we show that the metal ions at these two sites play very different roles. We argue that the metal ion at binding site 1 coordinates the attacking 2′-oxygen species in the reaction and lowers the pK(a) of the attached proton, thereby increasing the concentration of the attacking alkoxide nucleophile in an equilibrium process. In contrast, the role of the metal ion at binding site 2 is to catalyze the reaction by absorbing the negative charge that accumulates at the leaving 5′-oxygen in the transition state. We suggest structural reasons why the Mg(2+)–La(3+) ion combination is particularly suited to demonstrating these different roles of the two-metal ions in the ribozyme cleavage reaction.